Pembuatan Jamban Keluarga untuk Rumah Tangga dengan Kasus Stunting di Wilayah Kerja Puskesmas Wani - Sapriana Sapriana; Hanum Sasmita; Novarianti Novarianti (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The working area of the Wani Community Health Center has 193 cases of stunting in toddlers. One of the risk factors for stunting in toddlers is the use of family toilets. In Central Sulawesi, low birth weight, lack of handwashing behavior, and not having a toilet are risk factors for stunting in infants. Family toilets are an important sanitation facility for housing. The goal of this activity is to provide adequate sanitation facilities for defecation for one household that has a stunted toddler and for the household members to be able to use it. The method of community service is by practicing the construction of healthy toilets and providing education and discussion on healthy toilets to the community who have stunting cases. The target of the education is 20 mothers of stunted toddlers in the working area of the Wani Community Health Center, and after that, the utilization will be evaluated by household members. The results of this community service are the construction of one toilet facility and education to the community on the importance of toilets. The conclusion is that all household members should not dispose of waste in any place such as in rivers and behind houses as before. It is recommended that every household have a healthy toilet to break the chain of environmentally-based disease transmission.